Lab-on-a-chip technologies for minimally invasive molecular sensing of diabetic retinopathy. Issue 10 (29th April 2022) - Vieira, Maria; Fernandes, Rosa; Ambrósio, António F.; Cardoso, Vanessa; Carvalho, Mariana; Weng Kung, Peng; Neves, Miguel António Dias; Mendes Pinto, Inês
Abstract : Diabetic retinopathy (DR) is the most common diabetic eye disease and the worldwide leading cause of vision loss in working-age adults. Abstract : Diabetic retinopathy (DR) is the most common diabetic eye disease and the worldwide leading cause of vision loss in working-age adults. It progresses from mild to severe non-proliferative or proliferative DR based on several pathological features including the magnitude of blood–retinal barrier breakdown and neovascularization. Available pharmacological and retinal laser photocoagulation interventions are mostly applied in the advanced stages of DR and are inefficient in halting disease progression in a significantly high percentage of patients. Yet, recent evidence has shown that some therapies could potentially limit DR progression if applied at early stages, highlighting the importance of early disease diagnostics. In the past few decades, different imaging modalities have proved their utility for examining retinal and optic nerve changes in patients with retinal diseases. However, imaging based-methodologies solely rely on morphological examination of the retinal vascularization and are not suitable for recurrent and personalized patient evaluation. This raises the need for new technologies to enable accurate and early diagnosis of DR. In this review, we critically discuss the potential clinical benefit of minimally-invasive molecular biomarker identification and profiling of diabetic patients who are at risk of developing DR. We provide a comparative overview of conventional and recently developed lab-on-a-chip technologies for quantitative assessment of potential DR molecular biomarkers and discuss their advantages, current limitations and challenges for future practical implementation and continuous patient monitoring at the point-of-care.